Keterbacaan Catatan Atas Laporan Keuangan dan Dampak Audit (Readability over Financial Reporting Footnotes and Audit Outcomes) - Sagitarisma, Nadiah Bella; Wijaya, Riesanti E. (Akutansi Bisnis & Manajemen ( ABM ), 2021)
This study aims to find out the relationship of readability over financial reporting footnotes and audit outcomes. Audit outcomes are projected by audit fees and audit report lag. Researchers used data from the company's financial statements listed on IDX in 2015-2018. Researchers used purposive sampling. From the copying, researchers processed 184 company data. This study used the panel's data regression analysis method. Data processing uses Generalized - least - squares. This research proves that the worse the readability, the lower the audit fee. Meanwhile, the worse the readability, the more time it takes the auditor to carry out an examination of the financial statements. This phenomenon occurs because the condition of the readability of notes to financial statements in Indonesia is still at a low level.